Pembatasan Asas Kebebasan Berkontrak dalam Kontrak Baku Digital: Analisis Perlindungan Konsumen Pada Terms of Use Netflix - Raditiya Eka Putra Pratama; Zulfikar; Men Wih Widiatno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of information technology has encouraged the use of digital standard contracts through Terms of Use unilaterally drafted by service providers, including Netflix. This situation creates disparities in bargaining power because consumers can only accept or reject the entire agreement. This research aims to (1) analyze the imbalance of consumer positions in Netflix’s Terms of Use from the perspective of the principle of freedom of contract and (2) examine forms of legal protection for consumers. This research employs a normative legal method using statutory and conceptual approaches. Primary, secondary and tertiary legal materials are analyzed qualitatively using the deductive syllogism method. The results indicate that the Cancellation, Warranties and Limitations on Liability, Class Action Waiver and Changes to These Terms and Assignment clauses potentially create inequality between the rights and responsibilities of the parties involved by granting dominant authority to Netflix and limiting consumer rights. Normatively, consumer legal protection is provided under the Consumer Protection Law; however, its effectiveness still requires optimization to ensure a balance of positions between parties in digital standard contracts. Therefore, limitations on the principle of freedom of contract are necessary to establish a fair and balanced contractual relationship while providing legal certainty for consumers.